Efficiency and productivity performance of zakat funds in Algeria. Issue 3 (19th February 2018) - Djaghballou, Chams-Eddine; Djaghballou, Mohamed; Larbani, Mousa; Mohamad, Azhar
Abstract : Purpose: The purpose of this study is to examine the efficiency and productivity performance of zakat funds managed by Directorates of Religious Affairs and Endowments (DRAE) in Algeria. Design/methodology/approach: In this study, the authors employ data envelopment analysis and measure Malmquist Productivity Index for DRAE's input and output data spanning from 2003 to 2013. Findings: The authors find that total factor productivity has increased sharply for all zakat funds, mainly due to a technical rather than efficiency change. Further decomposition of the efficiency change into its pure technical and scale efficiency components suggests that the pure efficiency is a more important source of efficiency change than the scale efficiency component, meaning that zakat funds rely on technical aspects to gain efficiency. Originality/value: The findings of this study are expected to contribute considerably to the existing knowledge on the operating performance of zakat funds in Algeria.